Key performance indicators - Perl, J.; Memmert, D. (Modelling and simulation in sport and exercise, 2020)
Perl and Memmert start by discussing the meaning and usefulness of simple indicators like the number of passes or percentage of ball possession. Such indicators can be understood as a radical model-oriented reduction - often, incidentally, reducing or even erasing useful information in the process. From a modelling viewpoint, approaches are introduced that try to combine necessary reduction with protection of key information in order to indicate useful performance aspects. However, the challenge remains in finding the right balance between the precision of analysis results and identifying the best way to transfer interpretation of those results to the practice of playing in order to improve performance.